Implementation and Evaluation of a Haptic Playback System - Williams, Robert L.; Srivastava, Mayank; Conaster, Robert; Howell, John N. (Haptics-e, The electronic journal of haptics research, 2004)
This article presents implementation and evaluation of a haptic playback system using the PHANToM haptic inerface, in the context of our Virtual Haptic Back Project at Ohio University. Playback has the potential to improve virtual palpatory diagnosis training by allowing students to follow and feel an expert's motions prior to performing their own palpatory tasks. We have two modes in our playback system. In mode 1 the human is passive and experiences position playback of the expert's tactile examination via the PHANToM with a PD position controller. No haptics model is enabled in mode 1. In mode 2 the human traces the expert's path actively through visual cues. Mode 2 enables the haptics model so that the trainee feels approximately what the expert did in the original task. The experiment described in this article showed that performance with playback mode 2 is enhanced (i.e., there is less position error) when preceded by playback mode 1.